Increasing Parental Knowledge of Children's Nutrition Needs - Ismaniar Ismaniar; Nur Hazizah; Syuraini Syuraini (Universitas Negeri Padang, 2019)
Health is one of the conditions for a realized generation that is ready with a variety of future competition. Health affects development. Intake of nutritious food from an early age is a solution to health and avoid various diseases. Parents as full responsibility for the sustainability of children's growth and development need to have good knowledge about this and can provide the best service for children. But not all of them can fulfill it. The education and practice of cooking healthy food for early childhood carried out in college service activities can help improve agricultural knowledge and skills.Keywords: Knowledge, Parents, Nutritional Intake, Healthy Generation